The Aplication of Vibro – Abrasive Machining for Smoothing of Castings - Bańkowski, D.; Spadło, S. (Archives of Foundry Engineering, 2017)
The paper presents the production problems related to casting using precision casting methods. The essential adverse effect of the casting process is the presence of burrs understood as oversize material necessary to remove the next finishing operations. In addition, the surfaces of the cast often characterized by a porous structure. One of the methods to improve the smoothness of the area proposed by the authors is the use of vibro-abrasive finishing. This type of treatment is widely used in the treatment of finishing small objects as well as complex shapes. Objects in the form of casting in the first step was treated with aggressive deburring polyester matrix abrasive media. The second stage was polishing, with using smoothing porcelain media. The study evaluated the effect of vibro-abrasive machining typical cast on the basic parameters of the geometric structure of the surface. Observations using optical microscope Nicon Eclipse MA 200 compared changes in surface microstructure and the effect of deburring. Clearly we can say that vibro-abrasive machining an effective way of reducing the size of burrs, smoothing and lightening the surface of objects made by casting.
Keywords: Castings; Vibro-abrasive machining; Finishing; Burrs removal; Surface quality